2003
DOI: 10.1046/j.1365-2095.2003.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and body composition of rohu (Labeo rohita ) fed diets containing oilseed meals: partial or total replacement of fish meal with soybean meal

Abstract: A 56‐day feeding trial was conducted to evaluate growth, feed utilization and body composition of fingerling rohu, Labeo rohita (4.5 ± 0.2 cm; 2.58 ± 0.04 g), fed five isonitrogenous (350 g kg−1 crude protein) and isoenergetic (15.7 kJ g−1 metabolizable energy) diets in which the main protein contributors were: diet I, fish meal (FM); diet II, soybean meal (SBM); diet III, groundnut meal (GNM); diet IV, equal amounts of SBM, GNM and canola meal (CM); diet V, equal amounts of FM, SBM, GNM and CM. Fish were stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 25 publications
(25 reference statements)
3
29
0
Order By: Relevance
“…Lin and Luo (2011) reported a decrease in SGR and growth of tilapia, Oreochromis niloticus with an increase in dietary soybean meal. Similar results have been reported in L. rohita (Khan et al, 2003;Saeed et al, 2005;Ahmed et al, 2012), Barbodes altus (Elangovan and Shim, 2000), red tilapia (Moharram and Raky, 2007). However, Abid and Ahmed (2009) has reported contrasting results and found diet containing soybean and sunflower meal attained good growth than diet containing fish meal.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Lin and Luo (2011) reported a decrease in SGR and growth of tilapia, Oreochromis niloticus with an increase in dietary soybean meal. Similar results have been reported in L. rohita (Khan et al, 2003;Saeed et al, 2005;Ahmed et al, 2012), Barbodes altus (Elangovan and Shim, 2000), red tilapia (Moharram and Raky, 2007). However, Abid and Ahmed (2009) has reported contrasting results and found diet containing soybean and sunflower meal attained good growth than diet containing fish meal.…”
Section: Discussionsupporting
confidence: 77%
“…Brood stock nutrition of carps is one of the most poorly researched areas in aquaculture. So far few studies have been made on brood stock nutrition of carps (Singh and Dhawan 1996;Khan et al, 2003Khan et al, , 2005Anonymous 2006;Nandi et al, 2001Nandi et al, , 2007. To a large extent, this may be due to the necessity of suitable indoor or outdoor culture facilities for maintaining large groups of adult fish and the consequent higher cost of running and conducting extended brood stock feeding trials (Varghese et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Different oil seeds and legumes have already been tried in the carp diet as partial replacement of fish meal at the levels of 10-40% Ray 1996, 1999;Hossain et al 2001;Ramachandran et al 2005). Among several plant protein sources, soya bean cake was reported to be most efficiently utilized by the fingerlings of rohu when supplemented with methionine and fortified with minerals; though at their higher inclusion levels, the growth was reduced (Khan et al 2003;Xie et al 1998). Suboptimal amino acid balance, low protein contents and presence of antinutritional factors (ANFs) of plant ingredients seem to be responsible for the decrease in the growth of the fishes at their higher inclusion level in fish diet (Tacon 1997).…”
Section: Discussionmentioning
confidence: 92%
“…Inclusion of plant proteins in the diets of carp has shown that the partial replacement of fish meal is feasible. Most of the research has concentrated on the evaluation of legume seeds, oil seeds and their by-products like soya bean, groundnut oil cake, canola, moong, cowpea, guar, sesbania and similar other feed in diets of carps (Hossain et al 2001;Garg et al 2002;Khan et al 2003). The presence of antinutritional factors and deficiency of certain essential amino acids put limitations on the use of plant proteins as complete replacement of fish meal in the aqua feed (Tacon 1997).…”
Section: Introductionmentioning
confidence: 99%
“…High cost can be overcome by replacing animal origin feedstuffs with local available vegetable-derived protein ingredients. Many cultured warm-water fish, including carp, require no meat or fish products in their diets [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%